Outcome of isolated fetal choroid plexus cyst detected in prenatal sonography among infertile patients referred to Royan Institute: A 3-year study - Shohreh Irani; Firoozeh Ahmadi; Maryam Javam; Ahmad Vosough Taghi dizaj; Fatemeh Niknejad (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2015)
Background: Several studies have assessed the correlation of fetal choroid plexus cyst (CPC) and the risk of congenital anomalies, but few ones have discussed isolated CPC (with no other abnormal sonographic finding). Objective: The aim of this study was to determine the outcome of isolated fetal choroid plexus cyst and to specify its clinical significance. Materials and Methods: This cross sectional study was carried out at Royan Institute in Tehran, Iran, between April 2009 and December 2012. All prenatal sonographies in this period of time were assessed using a computerized database and fetuses who had isolated CPC were recruited in the study. Sonography reports, mother serum screening test results, fetal echocardiography and amniocentesis were evaluated until birth. A follow-up phone call was made to all individuals to learn about the neonatal outcomes. Results: Overall, 6240 prenatal sonographies were performed in this setting during this period. Isolated CPC was detected in 64 fetuses. The results of double test (N=30), triple test (N=5) and fetal echocardiography (N =24) were normal. Quadruple test result showed 3 abnormal out of 29 cases that all had normal karyotypes. Four samples were dropped out due to premature rupture of membranes (N=3) and intrauterine fetal death (N=1). It was found that the outcomes of all remaining fetuses (N=60) were normal and no anomaly ones were seen until birth. Conclusion: Isolated CPC is a benign regressive condition with no clinical significance.